CONTEXT-AWARE ARCHITECTURE USING MOBILE PHONE SIMULATOR: A CASE STUDY OF AN INSTITUTION (International Journal of Innovative Computing, 2014)
Abstract— Mobile phones nowadays are ubiquitous with our daily activities and the sensing ability of the device inspired us to provide context aware service to users in the academic environment. The paper presents the concept of a context aware solution using a proposed architecture in a theoretical approach. The context-aware solution is a notification that delivers a text or call about particular information dissemination on event or activity that occurs as a result of unexpected circumstance or situational changes in the institution on their mobile phone. The process is activated by a popup from the proxy server through the mobile portal database. This is follow up by a reminder from the server when necessary. This paper proffer solution to a perennial problems that normally occur from traditional method of bill board/or notice board placement of event such as examination time table/course schedule, as means of information dissemination to lecturers and students in the institution. The approach was simulated with phone simulator, and results shown to lecturers and students as presented in the paper were satisfactory.